Welfare Tracking in the Aftermath of Crisis : The Central Sulawesi Disaster Response - Purnamasari, Ririn Salwa; Febriady, Ade; Wirapati, Bagus A.; Farid, M. Noor; Milne, Peter; Kawasoe, Yasuhiro; Vun, Jian; Engstrom, Ryan; Nasiir, Mercoledi (World Bank, Jakarta, 2021)
The September 2018 earthquake, tsunami, and liquefaction in Central Sulawesi—the deadliest natural disaster to hit Indonesia since the 2004 Aceh tsunami—exposed challenges in accessing real-time data on what assistance, how much assistance, and where immediate assistance is needed for emergency relief, and the subsequent recovery and reconstruction phases. In response, the World Bank developed a Welfare Tracking in the Aftermath of Crisis (WelTrAC) tool, which employs a mixture of panel household survey data and remote-sensed satellite imagery data to integrate micro and macro levels of disaster impact and recovery assessments, and presents the updated findings regularly on an interactive web-based monitoring dashboard.